Exploring the Textual and Tactile Weave of Academic Subjectivities: Self-portraits, Intimacy, and Distance - Toll, Haley; Badenhorst, Cecile; McLeod, Heather (Art/Research International)

(untitled) (University of Alberta, 2023)
Within the neoliberal university, academics become positioned around market-driven managerialist ideologies and the techniques enacting those principles. Audit cultures actively and continuously measure and shape academic subjectivities defined by a specific kind of success. The market-driven individualistic model can conflict with ethical ideals and longings for self-expression, while the mismatch between institutional goals and personal values creates an academic self that is pulled in conflicting directions. We become subjects of the discourse but we can limit our subjectivity and develop authentic insight. In this paper, we engage in a process of embodied making. We create textual and tactile self-portraits as a way of pushing back at neoliberal subjectivities, and to make visible our multiple selves. Although we recognize that we are always a part of what we resist, we use making as a way to create micro-resistances for our own renewal. Our self-portrait assemblages and stories are ambiguous and fluid but capture a view of selves hidden beneath the professional self. We are reminded that we are creative beings, and that there is room within neoliberalism to open intentional spaces. We may not always succeed in seeing our contradictory identities, yet we are able to occasionally capture glimpses of our shifting selves.